Tissue-specific glycosylation in the honeybee: Analysis of the N-glycomes of Apis mellifera larvae and venom - Hykollari, Alba; Malzl, Daniel; Stanton, Rhiannon; Eckmair, Barbara; Paschinger, Katharina (Biochimica et biophysica acta. General subjects, 2019)
Previous glycophylogenetic comparisons of dipteran and lepidopteran species revealed variations in the anionic and zwitterionic modifications of their N-glycans; therefore, we wished to explore whether species- and order-specific glycomic variations would extend to the hymenoptera, which include the honeybee Apis mellifera, an agriculturally- and allergologically-significant social species. In this study, we employed an off-line liquid chromatography/mass spectrometry approach, in combination with enzymatic and chemical treatments, to analyse the N-glycans of male honeybee larvae and honeybee venom in order to facilitate definition of isomeric structures. The neutral larval N-glycome was dominated by oligomannosidic and paucimannosidic structures, while the neutral venom N-glycome displayed more processed hybrid and complex forms with antennal N-acetylgalactosamine, galactose and fucose residues including Lewis-like epitopes; the anionic pools from both larvae and venom contained a wide variety of glucuronylated, sulphated and phosphoethanolamine-modified N-glycans with up to three antennae. In comparison to honeybee royal jelly, there were more fucosylated and fewer Man4/5-based hybrid glycans in the larvae and venom samples as well as contrasting antennal lengths. Combining the current data on venom and larvae with that we previously published on royal jelly, a total honeybee N-glycomic repertoire of some 150 compositions can be proposed in addition to the 20 previously identified on specific venom glycoproteins. Our data are indicative of tissue-specific modification of the core and antennal regions of N-glycans in Apis mellifera and reinforce the concept that insects are capable of extensive processing to result in rather complex anionic oligosaccharide structures. [Display omitted] •In depth analysis of the N-glycomes of honeybee larvae and venom•Occurrence of fucose, glucuronic acid, phosphoethanolamine and sulphate modifications•Distinct N-glycomes as compared to royal jelly or to other insect species